The Implementation of Bamboozle to Enhance Interaction and Participation of Grade 7 Students in English Subjects at UPT SMPN 37 Medan - Zuleha, Jasmin; Aulia, Nabilah Fitri; Fahada, Nazli; Putra, Surya Kelana (Pusdikra Publishing, 2025)
This study explores the use of Bamboozle, a gamified digital platform, to enhance interaction and participation among Grade 7 students in English subject at UPT SMP Negeri 37 Medan. The research responds to low student engagement due to traditional textbook-based methods. In today’s digital era, technology presents opportunity to create more dynamic and effective learning experiences. Using a qualitative approach, data were collected through observation, bamboozle implementation, questionnaires, and interviews. Findings show that Bamboozle significantly improved student motivation, interaction, focus, and enjoyment in learning. Most students found the platform engaging and expressed a desire to use it more frequently in class. Overall, Bamboozle proved to be an effective tool in promoting active and collaborative learning.